Diversity of Vegetable Types Typical to Lombok Island in an Effort to Support Food Security in the Community - Immy Suci Rohyani; Ahmad Jupri; Suripto Suripto; Sukiman Sukiman; Kurniasih Sukenti (Jurnal Biologi Tropis, 2021)
The island of Lombok with the majority of its original inhabitants, namely the Sasak tribe, has known and used a number of plants as typical food or vegetables to complement the main menu. Typical vegetables are vegetables that are only found in an area, at a certain season and processed in a special way. Currently, the existence of vegetables typical of the island of Lombok is rarely found and some of them are starting to become extinct. This study aims to obtain data related to the diversity of species, economic value and distribution of typical vegetables on the island of Lombok. The information obtained is very much needed in building a data base that can be used as important information in the process of plant conservation and domestication. The research method used was an exploratory survey with a qualitative approach through a structured interview technique using a questionnaire that was presented orally. The research locations were all districts on the island of Lombok. The results showed that there were 53 types of vegetables typical of the island of Lombok. Trees are the most common types of habitus (17 species), then shrubs (16 species), herbaceous species (14) and 10 creeping types. Young leaves are part of the plant that is most widely used as a vegetable. Most of these vegetables are not traded and grow wild in forests or cultivated areas. The districts of East Lombok and Central Lombok are the areas where the most of these types of vegetables are found, while the city of Mataram is the area with the least. The small area and the lack of green open space are suspected to be the cause of the reduction in the typical vegetables found in the city of Mataram.